2018
DOI: 10.1371/journal.pone.0199204
|View full text |Cite
|
Sign up to set email alerts
|

Influence of citrate concentration on the activation of blood cells in an in vitro dialysis setup

Abstract: BackgroundRegional citrate anticoagulation has been associated with enhanced biocompatibility in hemodialysis, but the optimal dose of citrate remains to be established. Here, we compared parameters related to cellular activation during in vitro dialysis, using two doses of citrate.MethodsHuman whole blood, anticoagulated with either 3 mM or 4 mM of citrate, was recirculated in an in vitro miniaturized dialysis setup. Complement (C3a-desArg), soluble platelet factor 4 (PF4), thromboxane B2 (TXB2), myeloperoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
9
2
Order By: Relevance
“…Reduced complement activation with citrate anticoagulation was shown in apheresis [12] and during dialysis with cellulose membranes [21], but not with modern synthetic membranes [11]. Although our previous in-vitro data showed a trend towards lower complement activation at higher doses of citrate [17], the results of the present clinical study confirm that no significant activation of complement occurs during RCA even at the standard dose.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Reduced complement activation with citrate anticoagulation was shown in apheresis [12] and during dialysis with cellulose membranes [21], but not with modern synthetic membranes [11]. Although our previous in-vitro data showed a trend towards lower complement activation at higher doses of citrate [17], the results of the present clinical study confirm that no significant activation of complement occurs during RCA even at the standard dose.…”
Section: Discussioncontrasting
confidence: 60%
“…A significant reduction in clotting was reported with citrate compared to low molecular weight heparins and moderate doses of unfractionated heparin [20]. Our previous in vitro results also showed a significantly better score with an increased (4 mmol/L) dose of citrate, although the results were already very good at the lower dose [17]. The results of the present randomized study could not confirm the in vitro findings and showed no further improvement of the SEM clotting score with the increased dose of citrate.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations